Relationship between neutrophil-to-lymphocyte ratio, d-dimer and troponin-I values and pulmonary embolism severity index - Guzel, Murat; Ozgen, Emre; Terzi, Ozlem; Tevfik Demir, Mehmet; Yucel, Murat; Baydin, Ahmet (Annals of Medical Research, 2021)
None
Keywords: D-Dimer; Emergency; Neutrophil-To-Lymphocyte Ratio; Pulmoner Embolism; Pulmonary Embolism Severity Index; Troponin.